Budget Impact Of Including Avelumab As A Second-Line Treatment For Locally Advanced Or Metastatic Urothelial Cancer In The United States: Commercial And Medicare Payer Perspectives - Kongnakorn T; Bharmal M; Kearney M; Phatak H; Benedict A; Bhanegaonkar A; Galsky M (ClinicoEconomics and Outcomes Research, 2019)
Thitima Kongnakorn,1 Murtuza Bharmal,2 Mairead Kearney,3 Hemant Phatak,4 Agnes Benedict,5 Abhijeet Bhanegaonkar,4 Matthew Galsky6 1Evidence Synthesis, Modeling and Communication, Evidera, London, UK; 2Global Evidence and Value Development, EMD Serono, Inc. (A business of Merck KGaA, Darmstadt, Germany), Rockland, MA, USA; 3Global Evidence and Value Development, Merck KGaA, Darmstadt, Germany; 4US Health Economics and Outcomes Research, EMD Serono, Inc. (A business of Merck KGaA, Darmstadt, Germany), Rockland, MA, USA; 5Evidence Synthesis, Modeling and Communication, Evidera, Budapest, Hungary; 6Tisch Cancer Institute, Icahn School of Medicine at Mount Sinai, New York, NY, USACorrespondence: Murtuza BharmalGlobal Evidence and Value Development, EMD Serono, Inc. (A business of Merck KGaA, Darmstadt, Germany), Rockland, MA, USAEmail murtuza.bharmal@emdserono.comObjective: To estimate the budget impact of introducing avelumab as a second-line (2L) treatment option for patients with locally advanced or metastatic urothelial cancer (mUC) from the perspective of a US third-party payer (commercial and Medicare).Methods: A budget impact model (BIM) with a three-year time horizon was developed for avelumab. Efficacy and safety data were sourced from published literature and US package inserts. The analysis was conducted in collaboration with a specialist oncologist who validated clinical assumptions. Costs were based on the number of eligible patients, time-to-treatment failure, overall survival, adverse events (AEs), and projected market shares of various treatments.Results: In a hypothetical commercial health plan of 30,000,000 members, 884 patients were estimated to be eligible for 2L treatment over a three-year time period. Without avelumab, the total cost for treating patients with mUC was estimated to be US$70,268,035. The introduction of avelumab increased total costs by $73,438 (0.10% increase). In a hypothetical Medicare health plan of 30,000,000 beneficiaries, a total of 4,705 patients were estimated to be eligible for 2L treatment. Without avelumab, the total cost for treating patients with mUC was estimated to be $292,923,098 from a Medicare perspective; however, with avelumab, there was an increase of $719,324 (0.25% increase) in total costs. Results of the sensitivity analyses demonstrated a cost-neutral impact across all tested scenarios from both perspectives.Conclusion: The BIM estimated that avelumab would have a cost-neutral impact within a US commercial and a Medicare health plan. Overall, avelumab can be an affordable and valuable treatment option for patients with locally advanced or mUC in the 2L setting. These findings demonstrate a consistently favorable budget impact in both populations. Further studies should be conducted to more comprehensively assess the clinical and economic implications of adding avelumab to the treatment armamentarium of 2L mUC.Keywords: urothelial carcinoma, budget impact model, cost analysis, economic analysis, immuno-oncology, chemotherapy